2009
DOI: 10.1093/carcin/bgp245
|View full text |Cite
|
Sign up to set email alerts
|

n -3 Polyunsaturated fatty acids modulate carcinogen-directed non-coding microRNA signatures in rat colon

Abstract: We have hypothesized that dietary modulation of intestinal non-coding RNA [microRNA (miRNA)] expression may contribute to the chemoprotective effects of nutritional bioactives (fish oil and pectin). To fully understand the effects of these agents on the expression of miRNAs, Sprague-Dawley rats were fed diets containing corn oil or fish oil with pectin or cellulose and injected with azoxymethane (AOM, a colon-specific carcinogen) or saline (control). Real-time polymerase chain reaction using miRNA-specific pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 65 publications
6
126
0
1
Order By: Relevance
“…Moreover, research on the miRNA expression levels in CRC cell lines also provided similar significant results. In previous studies, similar results indicated that miR-192, -194 and -215 were downregulated in CRC cell lines and rat colon tissues (16,26,27). Furthermore, our studies revealed that the increased tumor size in CRC was closely correlated with the low expression of miR-192, -194 and -215.…”
Section: A B C D F Esupporting
confidence: 87%
“…Moreover, research on the miRNA expression levels in CRC cell lines also provided similar significant results. In previous studies, similar results indicated that miR-192, -194 and -215 were downregulated in CRC cell lines and rat colon tissues (16,26,27). Furthermore, our studies revealed that the increased tumor size in CRC was closely correlated with the low expression of miR-192, -194 and -215.…”
Section: A B C D F Esupporting
confidence: 87%
“…Several studies have examined the effect of dietary components in other in vivo models. Examination of the miRNA response in rats fed diets containing corn or fish oil with pectin or cellulose and injected with a carcinogen or saline control particularly demonstrated a novel role for fish oil in protecting the colon from carcinogen-induced miRNA dysregulation, rather than a role for fiber (46,47). Shah and colleagues (47) did however demonstrate that various dietary combinations and carcinogen exposure modulated a number of miRNAs, including miR17-92 cluster miRNAs and miR21 (47).…”
Section: Cancer Prev Res; 7(8) August 2014mentioning
confidence: 99%
“…Carcinogen significantly downregulated of five known tumor suppressor miRNAs, which were reversed upon exposure to n-3 PUFA [133]. Based on transfection experiments in vitro, tumor suppressor protein, PTEN was found to be targeted by oncogenic miR-21 in human colon cancer cells.…”
Section: Role Of Nutritive Natural Agents In the Regulation Of Mirnasmentioning
confidence: 97%
“…A study by Davidson et al evaluated the chemopreventive effects of n-3-Polyunsaturated fatty acids (n-3 PUFAs) on azoxymethane-induced colon cancer in rats [133] . Carcinogen significantly downregulated of five known tumor suppressor miRNAs, which were reversed upon exposure to n-3 PUFA [133].…”
Section: Role Of Nutritive Natural Agents In the Regulation Of Mirnasmentioning
confidence: 99%